A large‐scale epidemiological investigation on trematode infections in small ruminants in Bangladesh - Anita Rani Dey; Nurjahan Begum; Anisuzzaman; Md Taohidul Islam; Mohammad Zahangir Alam (Veterinary Medicine and Science, 2022)
Abstract Background The important trematode species in small ruminants: Paramphistomum sp., Fasciola spp. and Schistosoma spp. seriously affect the productivity of domestic ruminants in endemic areas. Methods In the present study, we identified the potential risk factors associated with trematodes infections in small ruminants in seven topographic zones of Bangladesh using simple sedimentation and modified Stoll’ ova counting technique. Results A total of 2440 samples were examined, where 965 were found positive with one or more trematode species with an overall prevalence of 39.5% (95% CI, 37.6%–41.5%) and intensity of infection was 264.77 ± 9.86 egg per gram of faeces. Three trematode species were identified namely Paramphistomum sp. (34.1%, 32.2%–36.0%), Fasciola spp. (7.5%, 6.5%–8.6%) and Schistosoma spp. (2.7%, 2.1%–3.5%). Prevalence of co‐infection was 4.8%. The spatial distribution of trematode infections varied from 29.5% to 53.6%. Univariate analysis revealed that physiological condition of females, body condition, farming system, deworming and season were significantly (p < 0.05) associated with trematodes infections in small ruminants. By multiple logistic regression model, three factors such as physiological condition of females (pregnant and lactating), poor body condition and animals without deworming were identified as potential risk factors for trematodes infection in small ruminants. Conclusion Trematode infections are prevalent in the study areas and Paramphistomum sp. is most common in different areas among the identified trematodes species. Government should take necessary action to appraise an effective control strategy of trematode infections in small ruminants.